2021
DOI: 10.1155/2021/5574966
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Backward Walking on Static Stability, Proprioception, Pain, and Physical Function of Patients with Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Objective. Impaired static stability and proprioception have been observed in individuals with knee osteoarthritis (KOA), which serves as a major factor increasing risk of fall. This study aimed to investigate the effects of backward walking (BW) on static stability, proprioception, pain, and physical function in KOA patients. Methods. Thirty-two subjects with knee osteoarthritis were randomly assigned to either an BW group (BG, n = 16) or a control group (CG, n = 16). The participants in the BG received combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
0
16
0
3
Order By: Relevance
“…Recent studies focused on the complementary therapies and integrative medicine for pain relief in patients with KOA. One study showed that backward walking is a pain-relief way [ 24 ]. In another study, the effect of herbal medicine was compared with NSAID therapy, as the topical application [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies focused on the complementary therapies and integrative medicine for pain relief in patients with KOA. One study showed that backward walking is a pain-relief way [ 24 ]. In another study, the effect of herbal medicine was compared with NSAID therapy, as the topical application [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In addition, previous studies of the effects of proprioceptive exercises in knee, ankle or shoulder osteoarthritis provide the foundation for the use of proprioceptive interventions in thumb OA. [17][18][19][20][21] Joint position sense (JPS) is often measured through active joint position sense (AJPS) and passive joint position sense (PJPS). JPS determines the ability for a person to perceive a presented joint angle and then, after the limb has been moved, to reproduce the same joint angle actively or passively.…”
Section: Introductionmentioning
confidence: 99%
“…More evidence is needed on the effects of proprioceptive neuromuscular facilitation training for individuals with symptomatic thumb CMCJ OA to determine the most effective intervention. Considering the positive effects of the proprioceptive approach in other joints, [17][18][19][20][21] we hypothesize that proprioceptive training for persons with thumb CMC OA may reduce pain intensity and improve JPS, hand function, and occupational performance. The main purpose of this investigation is to study the effectiveness of a proprioceptive training program as an adjunct therapy to traditional treatment for patients with thumb CMCJ OA relative to traditional treatment alone.…”
Section: Introductionmentioning
confidence: 99%
“…At present, postoperative physical therapies and treatments for patients with KOA from home and abroad mainly include a joint range of motion therapy, muscle strength training, proprioceptive training, gait training, physiotherapy, etc. (6)(7)(8), which are adjusted based on the conditions of the patients. Apart from proprioceptive therapy, other rehabilitation programs are time-tested and well-developed.…”
Section: Introductionmentioning
confidence: 99%